Simulation and response mechanism of potential geographical distribution of plateau pika Ochotona curzoniae under climate change - Yanni Song; Hainan Chong; Dawei Wang; Haijun Xiao (Global Ecology and Conservation)
With global warming, climate change had significant impacts on the distribution of species and their habitats. As one of the keystone species of the Qinghai-Tibet Plateau (QTP), the plateau pika Ochotona curzoniae plays a vital role in the alpine grassland ecosystem. Based on 750 distribution points, 20 environmental variables, and the Global Human Influence Index (IGHP) database, the geographic distribution trends of plateau pika under current and three future periods (2030 s, 2050 s and 2090 s) in related three climate scenarios (SSP126, SSP370 and SSP585) were simulated and analyzed. The results showed that: 1) Climate factors are the main factors changing the habitat selection of plateau pika, with the highest permutation contribution (28.5 %) and permutation importance (30.6 %) for isothermality of bio3. 2). The central and eastern parts of the QTP are potential distribution areas for plateau pika, with the current suitable area totaling 8.01 × 105 km2, accounting for 32.04 % of the QTP. 3) The suitable areas of plateau pika will gradually migrate to higher altitude areas, especially with more significant changes under high-emission scenarios (SSP370 and SSP585). 4) Human activities have relatively limited impacts on the distribution pattern of plateau pika, mainly manifested as suitability changes in some local areas. This study revealed the spatio-temporal distribution changes of plateau pika under different climate scenarios, which may help to better understand the response mechanism of other plateau organisms to environmental changes. This study provided a scientific basis for the management of keystone species and their ecosystem services in the QTP.